2016
DOI: 10.3393/ac.2016.32.6.221
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Morbidity and Mortality After Surgery for Intestinal Perforation

Abstract: PurposeAn intestinal perforation is a rare condition, but has a high mortality rate, even after immediate surgical intervention. The clinical predictors of postoperative morbidity and mortality are still not well established, so this study attempted to identify risk factors for postoperative morbidity and mortality after surgery for an intestinal perforation.MethodsWe retrospectively analyzed the cases of 117 patients who underwent surgery for an intestinal perforation at a single institution in Korea from Nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 34 publications
3
41
1
1
Order By: Relevance
“…In our study, there was a total of 10.8% mortality noted amongst subjects which was statistically significantly associated with POMPP score. This observation was fairly comparable to past study by Shin et al had who noted 12.8% mortality in 117 patients who underwent surgery for an intestinal perforation [13]. Additionally, mortality in study by Kemparaj et al [14%] was higher than our overall mortality whereas that noted in Bali et al was lower [7%].…”
Section: Methodssupporting
confidence: 91%
“…In our study, there was a total of 10.8% mortality noted amongst subjects which was statistically significantly associated with POMPP score. This observation was fairly comparable to past study by Shin et al had who noted 12.8% mortality in 117 patients who underwent surgery for an intestinal perforation [13]. Additionally, mortality in study by Kemparaj et al [14%] was higher than our overall mortality whereas that noted in Bali et al was lower [7%].…”
Section: Methodssupporting
confidence: 91%
“…There are several studies about the prognostic factors associated with mortality of colonic perforation. Each study showed that the mortality of patients was associated with factors including but not limited to serum albumin level, C-reactive protein level, acute renal failure, Mannheim Peritoneal Index, and American Society of Anesthesiologists physical status classification system score [2,[11][12][13][14]. Scoring systems such as POSSUM, P-POSSUM, CR-POS-SUM, Association of Coloproctology of Great Britain & Ireland mortality model were developed to assess the prognosis of colonic perforation.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis done by Shin K.Y. et al that included 739 patients showed that obesity is associated with more severe course of the disease, systemic complications, local complications and higher mortality rate than other groups (27).…”
Section: Discussionmentioning
confidence: 99%